Driving ta’awun and ukhuwwah through Malaysia Madani values in workplace diversity - Mhd. Sarif, Suhaimi; Yahya, Rohaziah; Firmansah, Yayan (KLiBEL, 2025)
In a globalized workplace, diversity is an essential force that enhances work productivity and organizational performance. Taawun (mutual cooperation) and ukhuwwah (mutual bonding) can drive effective diversity. This is especially strategic when supported by the values of Malaysia Madani. Thus, this study explores how workplace diversity can be driven by taawun (mutual cooperation) and ukhuwwah (mutual bonding) through the core values of Malaysia Madani. These core values, represented by the acronym MADANI, include keMampanan (sustainability), kesejAhteraan (prosperity), Daya cipta (innovation), hormAt (respect), keyakiNan (trust), and Ihsan (compassion). Each of these values plays a vital role in promoting a harmonious work environment, even amidst diversity. Through qualitative focus group discussions (FGDs) with a diverse group of staff members from Islamic universities across Southeast Asia, the informants argued that taawun and ukhuwwah are effective driving forces in aligning diverse groups of individuals with shared values in the workplace, via Malaysia Madani values. The ultimate goal of Malaysia Madani is to cultivate ukhuwwah among individuals from various backgrounds within the workplace. This aligns closely with the practice of ta'awun, as it fosters mutual cooperation and respect, despite differences in ethnicity, culture, and personal beliefs. However, the participants noted that one of the significant challenges in achieving this goal lies in the divergence of personal life goals, particularly the pursuit of al-Falah (success or victory), which varies across individuals due to their different life experiences and beliefs. For future research, the study recommends using mixed methods to enhance the results.